Assignment 11

course MTH 158

æˆÑ«§¦ùèäoÍêÀœì¶Û¯ÊÑ„§ˆ»Sw¨assignment #010

010. `query 10

College Algebra

06-18-2008

......!!!!!!!!...................................

14:46:47

1.1.20 (was 1.1.12). Explain, step by step, how you solved the equation 5y + 6 = -18 - y

......!!!!!!!!...................................

RESPONSE -->

5y + 6 = -18 - y

+y - 6 - 6 +y =

6y = -24

y = - 4

confidence assessment: 3

.................................................

......!!!!!!!!...................................

14:48:16

** STUDENT SOLUTION WITH INSTRUCTOR COMMENT: 5y + 6 = 18 - y

Subtract 6 from both sides, giving us

5y = 12 - y

Add y to both sides,

5y + y = 12 or 6y = 12

divide both sides by 6

y = 2

INSTRUCTOR COMMENT: This is correct for equation 5y + 6 = 18 - y but the equation as I note it is 5y + 6 = -18 - y.

If that's the correct equation the solution is found by practically the same steps but you end up with y = -4. **

......!!!!!!!!...................................

RESPONSE -->

And I had the equation 5y + 6 = -18 - y, so... yeah.

self critique assessment: 2

.................................................

......!!!!!!!!...................................

14:55:35

1.1.38 (1.1.44) (was 1.1.30). Explain, step by step, how you solved the equation (2x+1) / 3 + 16 = 3x

......!!!!!!!!...................................

RESPONSE -->

Multiply both sides by 3

3 [(2x+1) / 3 + 16] = 3x (3) =

6x + 3 + 48 = 9x

-6x -6x =

51 = 3x

x = 17

confidence assessment: 2

.................................................

......!!!!!!!!...................................

14:57:09

** STUDENT SOLUTION:

(2x + 1) / 3 + 16 = 3x

First, multiply both sides of the equation by 3

2x +1 + 48 =9x or 2x + 49 = 9x

subtract 2x from both sides.

49 = 7x

Divide both sides by 7

7 = x

**

......!!!!!!!!...................................

RESPONSE -->

understood

self critique assessment: 2

.................................................

......!!!!!!!!...................................

15:06:41

1.1.44 was 1.1.36. Explain, step by step, how you solved the equation (x+2)(x-3) = (x+3)^2

......!!!!!!!!...................................

RESPONSE -->

(x+2)(x-3) = (x+3)^2 =

x^2 - x - 6 = x^2 + 6x + 9

-x^2 -6x +6 -x^2 - 6x + 6 =

-7x = 15 =

x = -(15/7)

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:06:53

** STUDENT SOLUTION: (x+2)(x+3) = (x+3)^2

First, we use the distributive property to remove the parenthesis and get

x^2 - x - 6 = x^2 + 6x + 9

subtract x^2 from both sides,

-x - 6 = 6x + 9

Subtract 9 from both sides

- x - 6 - 9 = 6x or -x - 15 = 6x

add x to both sides

-15 = 7x

Divide both sides by 7

-15/7 = x

**

......!!!!!!!!...................................

RESPONSE -->

ok

self critique assessment: 3

.................................................

......!!!!!!!!...................................

15:29:27

1.1.52 (was 1.1.48). Explain, step by step, how you solved the equation x / (x^2-9) + 4 / (x+3) = 3 / (x^2-9)/

......!!!!!!!!...................................

RESPONSE -->

Multiply (x^2 - 9) * both sides...

(x^2-9) * x / (x^2-9) + 4 / (x+3) = 3 / (x^2-9)*(x^2-9) =

x + 4x^2 - 36 / x + 3 =

x + [4(x^2 - 9) / x + 3] = 3

x + 4 (x+3)(x-3) / x+3 = 3

x + 4(x - 3) = 3

x + 4x -12 = 3

5x -12 = 3

5x = 15

x = 3

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:29:43

** Starting with

x / (x^2 -9) + 4 / (x+3) = 3 / (x^2 -9), first factor x^2 - 9 to get

x / ( (x-3)(x+3) ) + 4 / (x+3) = 3 / ( (x-3)(x+3) ).

Multiply both sides by the common denominator ( (x-3)(x+3) ):

( (x-3)(x+3) ) * x / ( (x-3)(x+3) ) + ( (x-3)(x+3) ) * 4 / (x+3) = ( (x-3)(x+3) ) * 3 / ( (x-3)(x+3) ). Simplify:

x + 4(x-3) = 3. Simplify

x + 4x - 12 = 3

5x = 15

x = 3.

If there is a solution to the original equation it is x = 3. However x = 3 results in denominator 0 when substituted into the original equation, and division by 0 is undefined. So there is no solution to the equation.

When you multiplied both sides by x-3, if x = 3 you were multiplying by zero, which invalidated your solution **

......!!!!!!!!...................................

RESPONSE -->

ok

self critique assessment: 3

.................................................

......!!!!!!!!...................................

15:47:11

1.1.58 (was 1.1.54). Explain, step by step, how you solved the equation (8w + 5) / (10w - 7) = (4w - 3) / (5w + 7)

......!!!!!!!!...................................

RESPONSE -->

Multiply both sides by (10w -7)(5w +7)

(10w -7)(5w +7) * (8w + 5) / (10w - 7) = (4w - 3) / (5w + 7) * (10w -7)(5w +7)

(5w +7) * 8w +5 = 4w -3 * (10w -7)

40 w^2 + 25w + 56w +35 = 40w^2 - 30w - 28w + 21

81w +35 = 58w +21

-81w - 21 -81w -21 =

14 = -139w

w = -(139/14)

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:47:37

** STUDENT SOLUTION:

1) clear the equation of fractions by multiplying both sides by the LCM (10w - 7)(5W + 7)

After cancellation the left side reads:

(5w+7)(8w + 5)

After cancellation the right side reads:

(10w - 7)(4w - 3)

multiply the factors on each side using the DISTRIBUTIVE LAW

Left side becomes: (40w^2) + 81w + 35

Right side becomes: (40w^2) - 58w + 21

3) subtract 40w^2 from both sides

add 58w to both sides

subtract 35 from both sides

Rewrite: 139w = - 14 Now divide both sides by 139 to get w = - (14 / 139)

DER**

......!!!!!!!!...................................

RESPONSE -->

understood

self critique assessment: 3

.................................................

......!!!!!!!!...................................

15:53:24

1.1.70 (was 1.1.78). Explain, step by step, how you solved the equation 1 - a x = b, a <> 0.

......!!!!!!!!...................................

RESPONSE -->

divide both sides by x

1 - a x / x = b / x

1-a = b/x

This should be

(1 - a x) / x = b / x, since you are dividing the entire side by x.

(1-a) / x is 1/x - a/x, by the distributive law.

So your attempt to eliminate x from one side, which is a good attempt, doesn't quite work out.

multiply 1/b times both sides

1/b * 1-a = b/x * 1/b

x = 1-a / b

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:54:49

** Start with

1 -ax = b, a <> 0.

Adding -1 to both sides we get

1 - ax - 1 = b - 1, which we simplify to get

-ax = b - 1.

Divide both sides by -a, which gives you

x = (b - 1) / (-a). Multiply the right-hand side by -1 / -1 to get

x = (-b + 1) / a or

x = (1 - b) / a. **

......!!!!!!!!...................................

RESPONSE -->

Not fully understood

self critique assessment: 2

see my above note

.................................................

......!!!!!!!!...................................

16:05:53

1.1.82 (was 1.1.90). Explain, step by step, how you solved the equation v = g t + v0 for t.

......!!!!!!!!...................................

RESPONSE -->

v = g t + v0

-v0 - v0 =

v - v0 = g t now ( v - v0) / g = (gt) / g

t = v - v0 / g

confidence assessment: 1

.................................................

......!!!!!!!!...................................

16:06:16

** NOTE: v0 stands for v with subscript 0; the whole expression v0 stands for the name of a variable. It doesn't mean v * 0.

Starting with v = g t + v0, add -v0 to both sides to get

v - v0 = gt. Divide both sides by g to get

(v - v0) / g = t

}or

t = (v - v0) / g. **

......!!!!!!!!...................................

RESPONSE -->

ok

self critique assessment: 3

.................................................

......!!!!!!!!...................................

16:13:49

1.1.90 (was 1.2.18). Explain how you set up and solved an equation for the problem. Include your equation and the reasoning you used to develop the equation. Problem (note that this statement is for instructor reference; the full statement was in your text) scores 86, 80, 84, 90, scores to ave B (80) and A (90).

......!!!!!!!!...................................

RESPONSE -->

For the average score to be 80, all 5 must add up to 400.

For the average score to be 90, all 5 must add up to 450.

86, 80, 84, 90 add up to 340, so for a B Mike must get a 60 on his next test for an average of 400.

For an A Mike must get 110 on his next test for the average to be 450.

confidence assessment: 2

.................................................

......!!!!!!!!...................................

22:39:05

** This can be solved by trial and error but the only acceptable method for this course, in which we are learning to solve problems by means of equations, is by an equation.

Let x be the score you make on the exam.

The average of the four tests is easy to find:

4-test average = ( 86 + 80 + 84 + 90 ) / 4 = 340 / 4 = 85.

The final grade can be thought of as being made up of 3 parts, 1 part being the test average and 2 parts being the exam grade. We would therefore have

final average = (1 * test average + 2 * exam grade) / 3.

This gives us the equation

final ave = (85 + 2 * x) / 3.

If the ave score is to be 80 then we solve

(85 + 2 * x) / 3 = 80. Multiplying both sides by 3 we get

85 + 2x = 240. Subtracting 85 from both sides we have

2 x = 240 - 85 = 155 so that

x = 155 / 2 = 77.5.

We can solve

(340 + x) / 5 = 90

in a similar manner. We obtain x = 92.5.

Alternative solution:

If we add 1/3 of the test average to 2/3 of the final exam grade we get the final average. So (using the fact that the test ave is 85%, as calculated above) our equation would be

1/3 * 85 + 2/3 * x = final ave.

For final ave = 80 we get

1/3 * 85 + 2/3 * x = 80. Multiplying both sides by 3 we have

85 + 2 * x = 240. The rest of the solution goes as before and we end up with

x = 77.5.

Solving 1/3 * 85 + 2/3 * x = 90 we get x = 92.5, as before. **

......!!!!!!!!...................................

RESPONSE -->

understood

self critique assessment: 2

.................................................

......!!!!!!!!...................................

23:16:02

`Extra Question. Explain, step by step, how you can solve the equation x^3 + 6 x^2 - 7 x = 0 using factoring.

......!!!!!!!!...................................

RESPONSE -->

?

self critique assessment: 0

.................................................

......!!!!!!!!...................................

23:18:18

** Starting with

x^3 + 6 x^2 - 7 x = 0 factor x out of the left-hand side:

x(x^2 + 6x - 7) = 0. Factor the trinomial:

x ( x+7) ( x - 1) = 0. Then

x = 0 or x + 7 = 0 or x - 1 = 0 so

x = 0 or x = -7 or x = 1. **

......!!!!!!!!...................................

RESPONSE -->

ok

self critique assessment: 2

&#

Your response did not agree with the given solution in all details, and you should therefore have addressed the discrepancy with a full self-critique, detailing the discrepancy and demonstrating exactly what you do and do not understand about the given solution, and if necessary asking specific questions (to which I will respond).

&#

.................................................

......!!!!!!!!...................................

23:18:30

Add comments on any surprises or insights you experienced as a result of this assignment.

......!!!!!!!!...................................

RESPONSE -->

confidence assessment:

.................................................

&#

Very well-done, with good answers on most questions and good self-critiques on the exceptions.

&#